Increasing the Knowledge Capacity of Midwife About Active Management Placenta Drainage Through Video at PONED Aceh Besar Health Center - gustiana; Asriah (Institute of Computer Science (IOCS), 2022)
The Ministry of Health (Kemenkes) noted that the maternal mortality rate in Indonesia was 4,627 people in 2020. This number increased by 8.92 % from the previous year, 4,197 people. The leading cause of maternal mortality is postpartum hemorrhage. Efforts to prevent postpartum hemorrhage can be started early, namely active management of the third stage with placental drainage. The use of placental drainage aims to reduce the volume of the placenta, support the effectiveness of uterine contractions, and accelerate separation and expulsion. Not all midwives are aware of active management of the third stage with placental drainage. For this reason, it is necessary to strengthen midwives' knowledge about placental drainage in active management of the third stage through videos. This research uses a quasi-experimental design with a one-group posttest only design to determine the knowledge and skills of midwives about placental drainage. The population in this study were midwives who served at the PONED Aceh Besar Health Center. The sample was midwives who served at the Want Jaya, Sibreh, Montasik, Seulimum, and Lhoong Health Centers, totaling 99 midwives. The results showed a relationship between the midwife's knowledge about placental drainage and the midwife's skills with a P-value of 0.000 with an R-value of 0.872, which means that the relationship between the knowledge and skills of the midwife is solid. There was an increase in the average knowledge of midwives by 84.14 and the average skill of midwives by 75.81.